1984
DOI: 10.1007/bf01406814
|View full text |Cite
|
Sign up to set email alerts
|

A clinico-experimental study on various wrapping materials of cerebral aneurysms

Abstract: In this paper, we discuss the results of a systemic study of various materials so far used for wrapping, using the intracranial arteries of 43 mongrel dogs. The findings obtained are: Muscle, fascia and dura observed began to show necrotic and absorbable change within 1 to 2 months after operation, suggesting their unreliability. Bemsheet was superior in this study in adhesiveness to the vascular wall, highly contributory to constructing a firm reinforced wall by proliferating collagen fibres in the space of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 5 publications
0
6
0
3
Order By: Relevance
“…Histological examination of recurrent aneurysms has shown that arterial wall thinning and disruption of both the muscle layer and the internal elastic lamina may lead to local frailty of the arterial wall adjacent to the clipped aneurysm and may be the cause of the formation or recurrence of an aneurysm. 19,20,24,31,50 Reinforcement of the residual neck and abnormal arterial wall is thought to lower the incidence of aneurysm recurrence. 19,20,31,54 Several previous reports indicate that aneurysms can recur from residual aneurysm fragments, and even from apparently well-clipped aneurysms, 14,32,47,68,69 and early reports stress the value of microsurgical reinforcement of incompletely obliterated aneurysm walls.…”
Section: 68mentioning
confidence: 99%
See 1 more Smart Citation
“…Histological examination of recurrent aneurysms has shown that arterial wall thinning and disruption of both the muscle layer and the internal elastic lamina may lead to local frailty of the arterial wall adjacent to the clipped aneurysm and may be the cause of the formation or recurrence of an aneurysm. 19,20,24,31,50 Reinforcement of the residual neck and abnormal arterial wall is thought to lower the incidence of aneurysm recurrence. 19,20,31,54 Several previous reports indicate that aneurysms can recur from residual aneurysm fragments, and even from apparently well-clipped aneurysms, 14,32,47,68,69 and early reports stress the value of microsurgical reinforcement of incompletely obliterated aneurysm walls.…”
Section: 68mentioning
confidence: 99%
“…In histological as well as clinical studies, cotton has been found to be the most effective reinforcement material. 19,31,59 However, several reports have described complications associated with wrapping modalities, such as cranial neuropathy …”
Section: -18576771mentioning
confidence: 99%
“…In an other study, it was reported that biobond induced chronic inflammatory changes, necrosis of the media and fibrosis in a rat model 9) . Muslin gauze is regarded as an effective material by inducing fibrosis which reinforces the aneurysm sac, and possibly inducing intraluminal thrombosis 6,14) . On the other hand, it has caused foreign body reaction such as infection or granuloma 8,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, coiling the intra-aneurysm space has come into the spotlight as a more non-invasive treatment. However, when clipping or coiling is impossible, neurosurgeons have to decide on another treatment such as wrapping or aneurysm neck remodeling 6) . Many authors had reported the efficacy of the wrapping technique, and the rebleeding and regrowth rates in wrapped aneurysms [2][3][4]7,11,15,17) .…”
Section: Introductionmentioning
confidence: 99%
“…Several types of material have been used for wrapping. Autogenous material such as muscle, fascia or dura mater have been shown to adhere only slowly to the aneurysmal wall, giving inadequate early protection, and to be absorbed in the long term, giving poor long-term results [2,6,7,18,21,22]. Cotton derivatives, e.g., gauze and muslin, showed a better experimental adherence [6,22], good results in some [25,26] but a high incidence of rebleeding in other clinical studies [2,7], and were associated with optochiasmatic arachnoiditis and granuloma formation [9,16,19].…”
Section: Discussionmentioning
confidence: 99%